Experimenting With Environmental Materials In The Art Of Painting And Ceramics As An Introduction To Enhancing The Concept Of Environmental Sustainability Among King Faisal University Students - Samah Mohamed Abd El Naser Abouzeid, Yasser Mohamed Fadl Ebrahem (South Eastern European Journal of Public Health, 2025)
The current research aims to: Open new horizons for experimentation with environmental materials in Al-Ahsa governorate aiming to enhance the concept of environmental sustainability among graduate students at King Faisal University. According to a teaching plan Based on experimentation with environmental materials, for all graduate students at the master’s level, numbering (7) Students who represented the intentional research sample. The research followed the descriptive analytical approach and the quasi-experimental approach in conducting a student experiment in the field of plastic arts and another personal experiment in the field of ceramics. The Likert scale was used to clarify the level of students’ performance in experimenting with environmental materials on the surface of their artworks, through designing student work evaluation card research samples. The research results show that experimenting with environmental materials in the art of Painting helped raise awareness of environmental materials among master's students and enhance the concept of sustainability in their paintings. Experimenting with environmental materials on the surface of ceramic works, whether before or after firing, resulted in unique and diverse textures and effects.